Maternal obesity and Caesarean delivery in sub‐Saharan Africa. Issue 7 (16th May 2016) - Cresswell, Jenny A.; Campbell, Oona M. R.; De Silva, Mary J.; Slaymaker, Emma; Filippi, Veronique
Abstract: Objectives: To quantify maternal obesity as a risk factor for Caesarean delivery in sub‐Saharan Africa. Methods: Multivariable logistic regression analysis using 31 nationally representative cross‐sectional data sets from the Demographic and Health Surveys (DHS). Results: Maternal obesity was a risk factor for Caesarean delivery in sub‐Saharan Africa; a clear dose–response relationship (where the magnitude of the association increased with increasing BMI) was observable. Compared to women of optimal weight, overweight women (BMI 25–29 kg/m 2 ) were significantly more likely to deliver by Caesarean (OR: 1.54; 95% CI: 1.33, 1.78), as were obese women (30–34.9 kg/m 2 (OR: 2.39; 95%CI: 1.96–2.90); 35–39.9 kg/m 2 (OR: 2.47 95%CI: 1.78–3.43)) and morbidly obese women (BMI ≥40 kg/m 2 OR: 3.85; 95% CI: 2.46–6.00). Conclusions: BMI is projected to rise substantially in sub‐Saharan Africa over the next few decades and demand for Caesarean sections already exceeds available capacity. Overweight women should be advised to lose weight prior to pregnancy. Furthermore, culturally appropriate prevention strategies to discourage further population‐level rises in BMI need to be designed and implemented.